Effect Of Abc Running Drill on the 50 Meter Sprint Of Students - Mimi Haetami; Andika Triansyah (Universitas Suryakancana, 2021)
The purpose of this study was to determine whether there is an effect of the abc running drill on the ability to sprint 50 meters. The research was conducted using an experimental method with one group pretest-posttest design. At the initial stage, data collection was carried out to determine the initial conditions of students' sprint abilities which included the ability of basic running techniques and 50 meters sprint speed. Data collection techniques using observation and tests. Observations were made by observing basic squat start techniques, running techniques and finishing techniques while the test was used to take a sprint time of 50 meters. The instrument used in the study used a rubric for the assessment of the 50 meter sprint ability. To calculate the data obtained, the Wilcoxon nonparametric test data analysis was used. Based on the results of data analysis, the Asym.Sig. (2-tailed) <0.05, then Ha is accepted. Asym.Sig. (2-tailed) (0.000 <0.05) means that there is an effect of abc running drill on the ability of students to sprint 50 meters.Keywords: Abc Running Drill, 50 Meter Sprint, Students